2022
DOI: 10.1007/s00395-022-00942-7
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged cardiac NR4A2 activation causes dilated cardiomyopathy in mice

Abstract: Transcription factors play a fundamental role in cardiovascular adaptation to stress. Nuclear receptor subfamily 4 group A member 2 (NR4A2; NURR1) is an immediate-early gene and transcription factor with a versatile role throughout many organs. In the adult mammalian heart, and particularly in cardiac myocytes, NR4A2 is strongly up-regulated in response to beta-adrenergic stimulation. The physiologic implications of this increase remain unknown. In this study, we aimed to interrogate the consequences of cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The NR4As pathway are having the role of controlling the extent of the inflammatory response for activating Estrogen productions through activating Acyl-COA-beta for promoting GCs-beta, B-arrestins synthesis (where NR4As are nuclear resonance or β-arrestin2 biosensors) which followed by Nrf2 production which activate ACE functions for Ang2-AT2 synthesis followed by VEGF-A productions "respectively" for anti-inflammatory growth and processes. The NR4A nuclear receptors sub-family (Nur77, Nurr1 and NOR-1) are emerging as important key in cardiac stress responses and adoptions; Where Nur77 seems to be a promising target in HF characterization and Therapy [6]. And in the heart itself the Nur77 is emerging as a key player in adverse cardiac remodeling [7].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The NR4As pathway are having the role of controlling the extent of the inflammatory response for activating Estrogen productions through activating Acyl-COA-beta for promoting GCs-beta, B-arrestins synthesis (where NR4As are nuclear resonance or β-arrestin2 biosensors) which followed by Nrf2 production which activate ACE functions for Ang2-AT2 synthesis followed by VEGF-A productions "respectively" for anti-inflammatory growth and processes. The NR4A nuclear receptors sub-family (Nur77, Nurr1 and NOR-1) are emerging as important key in cardiac stress responses and adoptions; Where Nur77 seems to be a promising target in HF characterization and Therapy [6]. And in the heart itself the Nur77 is emerging as a key player in adverse cardiac remodeling [7].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…That the Prolonged primary nuclear factor means dysfunction in some of followed activated steps for modulating proinflammation and GPCRs , that can be the result of causing mutation(due to accumulation) in pro-inflammation which will stimulate Tumor growth factor and will cause un-adopted growth which can lead to dilated cardiomyopathy. Where it is reported that prolonged cardiac NR4A2 activation causes dilated cardiomyopathy in mice [8].…”
Section: That the Nrs And Exercise-induced Muscle Remodeling [2]mentioning
confidence: 99%
“…Nuclear receptor subfamily group A member 2 (NR4A2), also known as NURR1, is an orphan nuclear receptor belonging to the NR4A family of receptors [ 23 ]. Previous studies have suggested that NR4A2 regulates the pathogenesis of various heart diseases, including diabetic cardiomyopathy, cardiac hypertrophy, left ventricular dilation, and heart failure by modulating the autophagy flux, cardiac metabolism, and hemodynamics [ 24 , 25 , 26 ]. However, the roles of NR4A2 in myocardial I/R injury are controversial [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%